Subconjunctival hemorrhage: risk factors and potential indicators - Tarlan B (Dove Medical Press, 2013)
Bercin Tarlan,1 Hayyam Kiratli21Department of Ophthalmology, Kozluk State Hospital, Batman, Turkey; 2Ocular Oncology Service, Hacettepe University Schoolof Medicine, Ankara, TurkeyAbstract: Subconjunctival hemorrhage is a benign disorder that is a common cause of acute ocular redness. The major risk factors include trauma and contact lens usage in younger patients, whereas among the elderly, systemic vascular diseases such as hypertension, diabetes, and arteriosclerosis are more common. In patients in whom subconjunctival hemorrhage is recurrent or persistent, further evaluation, including workup for systemic hypertension, bleeding disorders, systemic and ocular malignancies, and drug side effects, is warranted.Keywords: subconjunctival hemorrhage, contact lens, hypertension, red eye